KONTRIBUSI GOLONGAN BAHAN MAKANAN TERHADAP KONSUMSI ENERGI DAN PROTEIN RUMAHTANGGA DIINDONESIA - Sri Prihatini; Abas Basuni Jahari (Persagi, 2010)
Background: Some of the nutrition problems in Indonesia often as consequence of daily food consumption has not balanced, there is contribution more from cerealia than animal especially in poor families. Objectives: The aimed of this analysis is to studies the contribution of food group to household energy and protein consumption in Indonesia. Methods: Food consumption data of 173471 households sample of Health Research Data Base 2007 were calculated by Nutrisoft program developed by Research and Development Centre of Food and Nutrition. Food-stuff is categories to 8 group of food-stuff that is: Grains, Corms, Animal, Oil/Fat, Beans, Sugar, Fruit/fatty seeds and fruits and vegetables. Each group of food-stuff is calculated for the contribution to household consumption of energy and protein. Data were analyzed by descriptively. Results: At national level, the grains contributed of highest energy (67.2%) from household energy consumption, except in Papua, where contribution of grain equal to contribution of corms that is each 40%. The grains also gives highest contribution that is 44.7% from household protein consumption. In urban, the contribution of grain is 63.2% from household energy consumption while in rural is 68.6 %. In Urban, contribution of grain is 40% of household protein consumption, while in rural is 46.0%. Conclusions: The grains has the highest contribution for household energy and protein consumption. The protein from animal is only 38.7% and beans is 4.25%. Keywords: food-stuff, household energy protein consumption, contribution.